THE RESEARCH PROCESS OF SELF-STABILIZATION OF VERTICAL OSCILLATIONS IN A SYSTEM OF ELECTRODYNAMIC LEVITATION - Buriak, O. O.; Dzenzerskyi, V. O.; Zeldina, E. O. (Science and Transport Progress, 2007)
Based on the energy model for researching the processes of self-stabilization of the electrodynamics levitation systems, the authors studied the impact of the magnetic flux separation in the on-board magnet, as well as in the electrical buffer, rigidly bound to the magnet, and its effects on the residual oscillation energy level. It was demonstrated that the examined magnetic levitation system could effectively reduce the vertical oscillation without the use of any additional damping devices.